Influence Welfare Economy and Satisfaction Work Regarding Power Teacher Competition with Motivation Achievement as an Intervening Variable - Andi Emil Salim; Romansyah Sahabuddin; Agussalim Agussalim (Universitas Hamzanwadi, 2025)
Research This aim analyze influence welfare economy and satisfaction Work to Power teacher competition, good in a way direct and through motivation achieve as variables mediation. Research quantitative This involving 115 civil servant teachers State Civil Servants (ASN) consisting of for civil servants and PPPK at the level Elementary School, School Puff First and School State Senior High Schools in Makassar City in 2025. Questionnaire Instrument Data Google Form based developed from the grand theory of each variable, then analyzed using Structural Equation Modeling (SEM) with device SmartPLS-4 software. Testing the entire measurement model construct fulfil criteria validity convergent, validity discriminant, and reliability, so that worthy used in structural model testing. The results of the structural model analysis show that welfare economy, satisfaction work and motivation achieve influential positive and significant to Power teacher competition. Besides that, motivation achievement and satisfaction Work proven mediate in a way significant connection between welfare economy with Power teacher competition